A closer look at the subordinate population within the visible burrow system - Melhorn, Susan J (Physiol Behav, 2017)
The visible burrow system (VBS) utilizes the natural social behavior of rodents to model chronic social stress. Classically, when male and female rats are housed together in the VBS a dominance hierarchy rapidly forms with one dominant (DOM) and three subordinate (SUB) males. SUB animals show signs of chronic social stress, including loss of body weight and elevated basal corticosterone. This study furthered examined differences among the SUB population. Quantitative observations across numerous VBS colonies within the Sakai Lab suggest that there is variability in the effects of stress on the SUB population, specifically that some animals may experience more severe effects of chronic social stress than others. To further examine this observation, SUB animals were classified as OMEGA if they received a disproportionate amount of their colonies’ wounds. OMEGA animals received more wounds to their body compared to SUB (P<0.0001) and lost significantly more weight throughout the stress period compared to all other VBS-housed animals (group × time interaction P<0.0001). Following VBS housing it was determined the OMGEA also lost lean body mass (P<0.01 vs. controls and DOM), are hyporesponsive to an acute restraint challenge (P<0.01 vs all other groups) and show depressive-like behavior during a forced swim test. Furthermore, expression of neuropeptide Y within the amygdala, known for anxiolytic properties following chronic stress, was elevated among OMEGA (group × region interaction P<0.001). Together these observations suggest that an additional phenotype exists among the SUB animals within a VBS colony and represents the variability of the effects of chronic social stress.